Molecular mechanisms of resistance to Myzus persicae conferred by the peach Rm2 gene: A multi-omics view - Le Boulch, Pauline; Poëssel, Jean-Luc; Roux, David; Lugan, Raphaël (Frontiers in Plant Science, 2022)
The transcriptomic and metabolomic responses of peach to Myzus persicae infestation were studied in Rubira, an accession carrying the major resistance gene Rm2 causing antixenosis, and GF305, a susceptible accession. Transcriptome and metabolome showed both a massive reconfiguration in Rubira 48 hours after infestation while GF305 displayed very limited changes. The Rubira immune system was massively stimulated, with simultaneous activation of genes encoding cell surface receptors involved in pattern-triggered immunity and cytoplasmic NLRs (nucleotide-binding domain, leucine-rich repeat containing proteins) involved in effector-triggered immunity. Hypersensitive reaction featured by necrotic lesions surrounding stylet punctures was supported by the induction of cell death stimulating NLRs/helpers couples, as well as the activation of H2O2-generating metabolic pathways: photorespiratory glyoxylate synthesis and activation of the futile P5C/proline cycle. The triggering of systemic acquired resistance was suggested by the activation of pipecolate pathway and accumulation of this defense hormone together with salicylate. Important reduction in carbon, nitrogen and sulphur metabolic pools and the repression of many genes related to cell division and growth, consistent with reduced apices elongation, suggested a decline in the nutritional value of apices. Finally, the accumulation of caffeic acid conjugates pointed toward their contribution as deterrent and/or toxic compounds in the mechanisms of resistance.